2021
DOI: 10.1136/jnnp-2021-326386
|View full text |Cite
|
Sign up to set email alerts
|

Silent progression of brain atrophy in aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder

Abstract: ObjectiveTo investigate longitudinal brain atrophy in patients with neuromyelitis optica spectrum disorder (NMOSD).MethodsWe investigated the longitudinal brain atrophy rate in patients with aquaporin-4 antibody-positive NMOSD (AQP4+NMOSD) and those with multiple sclerosis (MS) in a retrospective cohort study. Brain volume was calculated with statistical parametric mapping-12.ResultsWe enrolled 36 patients with AQP4+NMOSD and 60 with MS. Patients with NMOSD were older and had a higher Kurtzke’s expanded disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…30 First myelitis attack can be associated with asymptomatic spinal cord MRI lesions in seropositive NMOSD patients (STM rather than LETM), but these silent lesions have also been described in patients with ON in the absence of prior myelitis. 31 In this study, we found that one-quarter of patients experienced asymptomatic STM lesion during the relapsefree period. In addition to this, spinal cord atrophy and reductions of mean upper cervical cord area have been reported in seropositive NMOSD, even in the absence of a clinical history of relapses or previous spinal cord MRI lesions.…”
Section: Discussionmentioning
confidence: 57%
“…30 First myelitis attack can be associated with asymptomatic spinal cord MRI lesions in seropositive NMOSD patients (STM rather than LETM), but these silent lesions have also been described in patients with ON in the absence of prior myelitis. 31 In this study, we found that one-quarter of patients experienced asymptomatic STM lesion during the relapsefree period. In addition to this, spinal cord atrophy and reductions of mean upper cervical cord area have been reported in seropositive NMOSD, even in the absence of a clinical history of relapses or previous spinal cord MRI lesions.…”
Section: Discussionmentioning
confidence: 57%
“…Volumetric data related to the study of NMOSD have contributed to our understanding of the impact of the disease on cortical gray matter, 15 deep gray matter, 16,17 hippocampal, 18,19 brainstem, 20 and whole brain volume measures. 21 The incorporation of texture adds an alternative form of information to volume change alone. This approach also enables the identification of early spatial pattern changes within Central to the pathophysiology of NMOSD are AQP4-IgG antibodies that bind selectively to the mercurial-insensitive 22 water sensitive transporting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric data related to the study of NMOSD have contributed to our understanding of the impact of the disease on cortical gray matter, 15 deep gray matter, 16,17 hippocampal, 18,19 brainstem, 20 and whole brain volume measures 21 . The incorporation of texture adds an alternative form of information to volume change alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent optical coherent tomography and visual evoked potential studies suggested subclinical neurodegeneration in NMOSD patients ( 101 , 102 ). More recently, silent progression of brain atrophy was documented in NMOSD patients, even in clinically inactive patients ( 103 ). Additional studies on blood GFAP levels further support the concept of ongoing subclinical neurodegeneration in NMOSD.…”
Section: Gfap In Blood As a Biomarker For Nmosdmentioning
confidence: 99%
“…The value of NfL may be more pronounced elsewhere. Given that NfL is a neuronal structural component, serum NfL might be a better biomarker for monitoring the degree of neurodegeneration of NMOSD ( 101 103 ) and associated cognitive impairment ( 113 ) than serum GFAP. This possibility should be elucidated in future studies.…”
Section: Special Considerationsmentioning
confidence: 99%